Evaluation of the biodiversity of the colombian coffee growing region present on the Cenicafé arthropods collection - CRUZ-B., CÉSAR AUGUSTO; POSADA-F., FRANCISCO (Revista Colombiana de Entomología, 2003)
The aim of this research was to organize the entomological material deposited at Cenícafes arthropod collection (CAC). For each specie, we performed museum curatory, phylogenetic organization, and recordings of the information gathered in the field, laboratory, and bibliographic resources. This information was used to create a database that enabled analysis using SAS program for descriptive statistics. The information in regards to the collection, depository, and identification was analyzed by curatory, using an evaluation system of 10 levels (ESL). The CAC has 5.843 specimens that belong to 16 insect orders, 103 families and 1.028 species, 639 of which were identified at specíes level, The species deposited at CAC were classified as beneficial ( insects (48,6%), harmful insects (48,9%) and the remaining 2,5 % could not be determined. According to the collection site, 78,1% of insects come from the Caldas department and were collected mainly in plants such as coffee, palms, and Erythrina. When the ESL was applied to the identify species (639), we found that 45% of them were in level 3; 9% in level 5, and 46% on level 7. The information from the specíes in level 7 can be used to prepare papers and reports. This level includes butterflies, moths, ants, leafhoppers, beetles and mantids.